2017
DOI: 10.1186/s12879-017-2324-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytokine profiling in Chagasic patients according to their arrhythmogenic-status

Abstract: BackgroundChagas disease is caused by the protozoan Trypanosoma cruzi and is characterized by heart failure and sudden death. Identifying which factors are involved in evolution and treatment response is actually challenging.Thus, the aim of this work was to determine the Th1/Th17 (IL-6, IL-2, TNF, IL-17 and IFN-γ) and Th2 (IL-4 and IL-10) serum profile in Venezuelan Chagasic patients stratified according amiodarone treatment, hypertension and arrhythmias.MethodsSera from 38 chagasic patients were analyzed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The consequence of myofibroblast differentiation is the increased expression and deposition of ECM proteins that further contribute to the fibrotic process [ 16 ]. Inflammation and fibrosis are hallmarks of CCC [ 6 , 34 36 ], with production of cytokines that contribute to pathogenesis [ 37 ] and co-localization of T. cruzi DNA or antigens with inflammatory infiltrate and fibrosis in cardiac tissue was also observed [ 6 , 7 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of myofibroblast differentiation is the increased expression and deposition of ECM proteins that further contribute to the fibrotic process [ 16 ]. Inflammation and fibrosis are hallmarks of CCC [ 6 , 34 36 ], with production of cytokines that contribute to pathogenesis [ 37 ] and co-localization of T. cruzi DNA or antigens with inflammatory infiltrate and fibrosis in cardiac tissue was also observed [ 6 , 7 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of Th1 and Th17 responses to T. cruzi infection is highlighted by the observation that selective downregulation of Th1 cells and Th17 cells by parasite trans-sialidases or the expression of other immunomodulatory factors promotes both host survival and low-level parasite persistence by reducing both protective and harmful effects (113,116). Levels of IFN-γ, IL-2, and IL-10 may predict the risks of arrhythmia and sudden death in Chagas patients, with elevated IL-2 most strongly correlated with a high risk of death (117). However, the frequency of activated T cells is inversely related to disease severity, and chronic infection may lead to clonal exhaustion and reduced numbers of memory T cells (118)(119)(120)(121).…”
Section: Adaptive Immunity To T Cruzi Infectionmentioning
confidence: 99%
“…In addition, IL-22, a pleiotropic cytokine mainly produced by T H 17 cells, is secreted in response to T. cruzi infection in mice, in an IL-23-dependent fashion, which seems to contribute to the regulation of inflammatory cytokines ( 198 ). With regards to human patients, the panorama is less clear: while some authors have shown that a higher frequency of IL-17 + cells within the CD3 + CD4 + subset of PBMC is associated with milder forms of the disease ( 99 , 199 ), and a correlation of IL-17A plasma levels with better cardiac function ( 200 ), others found increased levels of IL-17 in the sera of patients with higher risk of sudden death ( 201 ). However, it should be kept in mind that, as it was discussed above, T H 17 are not the only cell lineage producing IL-17 in response to T. cruzi .…”
Section: Adaptive Immunitymentioning
confidence: 99%